Analysis of Quality Management in Improving Product Quality: A Case Study of UD Ramayana Agro Mandiri, Batu City - Marisa Marisa; Siti Saroh; Rio Era Deka (CV. Proaksara Global Transeduka, 2025)
Increasingly tight business competition demands companies to be able to produce quality products to meet customer needs and expectations. Management of Quality is an important strategy in maintaining consistent product quality, increasing customer satisfaction, and strengthening company competitiveness. This study aims to analyze the implementation of Management of Quality in improving product quality and describe the obstacles and solutions implemented at UD. Ramayana Agro Mandiri, Batu City. The study uses a qualitative approach with a case study type. Data were obtained through observation, semi-structured interviews with the owner, admin, production division, packaging division, and documentation as supporting data. Data analysis uses the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The research findings indicate that the company has implemented seven principles of Management of Quality, namely customer focus, leadership, employee involvement, a process-based approach, continuous improvement, data-based decision making, and relationship management. Obstacles faced include raw material incompatibility, business competition, and the continued discovery of products that do not meet quality standards. The implemented solutions include a raw material return system, quality control, periodic evaluation, and stricter supervision of the production and packaging processes. The conclusion is that the implementation of Quality Management has been running well because it is able to maintain product quality consistency, minimize product non-conformities, increase consumer satisfaction, and support the company’s competitiveness.